1996
DOI: 10.1097/00007890-199612270-00029
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-4 in the Induction Phase of Allogeneic Neonatal Tolerance1,2

Abstract: We previously reported that prolonged graft survival in neonatally tolerant mice was associated with enhanced Th2/Th1 cytokines. To determine whether Th2 CD4 cells function in tolerance, we examined whether we could prevent tolerance by blocking Th2 CD4 maturation, using anti-interleukin (IL)-4 monoclonal antibody treatment during neonatal antigen exposure. Anti-IL-4 treatment restored the ability BALB/c of mice to reject A/J skin grafts and blocked the induction of tolerance through multiple mechanisms. Anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 36 publications
2
29
1
Order By: Relevance
“…(Schurmans et al, 1990;Donckier et al, 1995;Gao et al, 1996). Together with our splenectomy experiments, this would suggest that Th2 dominance must be established during primary responses in the lymph nodes.…”
Section: Neonatal Lymph Nodes Are Sufficient To Generate and Maintainsupporting
confidence: 58%
See 3 more Smart Citations
“…(Schurmans et al, 1990;Donckier et al, 1995;Gao et al, 1996). Together with our splenectomy experiments, this would suggest that Th2 dominance must be established during primary responses in the lymph nodes.…”
Section: Neonatal Lymph Nodes Are Sufficient To Generate and Maintainsupporting
confidence: 58%
“…It has been shown that IL-4 production in vivo is necessary for the induction and maintenance of neonatally induced tolerance to semiallogeneic F1 cells (Schurmans et al, 1990;Donckier et al, 1995;Gao et al, 1996). Thus, we next tested whether the splenic Th2 dominant responses are required for the induction of tolerance to alloantigens.…”
Section: Neonatal Lymph Nodes Are Sufficient To Generate and Maintainmentioning
confidence: 98%
See 2 more Smart Citations
“…To test this, we blocked in vivo IL-4 cytokine that serves as a growth and differentiation factor for Th2 cells (21). IL-4 was neutralized at the time of activation of type 2 CMspecific T cells using a protocol previously described by others (22). Recipient A.TL mice were injected i.p.…”
Section: Prevention Of Acute Rejection In Cm/ifa-treated Mice Dependsmentioning
confidence: 99%